Analysis of the Pedagogical Competence of Islamic Education Teachers in Improving Student Understanding in Madrasah Aliyah - Khansa Auliya Halizzah; Chusniatun, Chusniatun (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Islamic Religious Education (PAI) affects students' morals, attitudes, and understanding. The pedagogic ability of teachers to supervise the learning process has an impact on the effectiveness of PAI teaching. The purpose of this study is to analyze the pedagogic competence of PAI teachers in managing learning and its impact on students' religious understanding and development. This research uses phenomenological, qualitative, and field research methodologies. Teachers of Islamic Cultural History (SKI), Al-Qur'an Hadith, Fiqih, and Aqidah Akhlak acted as supporting informants. Observation, in-depth interviews, and documentation are the methods used to collect data. Technical triangulation is used to assess the validity of the data, while data reduction, data presentation, and conclusion drawing are used to analyze the data. As a result of the research, Islamic Religious Education (PAI) teachers at MA Al-Islam Jamsaren Surakarta have successfully applied their pedagogic skills. This is evidenced by the ability of teachers to prepare lessons, choose various contextual strategies and techniques, use dialogical learning, and conduct continuous evaluation and learning exercises. Students' understanding in the cognitive, emotional, and psychomotor realms is positively influenced by the teacher's pedagogic competence. The pedagogic competence of Islamic Religious Education (PAI) teachers is supported by a number of elements, including educational background, teaching experience, support from school policies, and the availability of learning infrastructure and facilities. On the other hand, limited time for learning activities and variations in students' motivation and learning capacity are limiting factors.